2011
DOI: 10.1097/prs.0b013e318208d00f
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Clinically Used Antiseptics and Wound Irrigating Agents in Combination with Wound Dressings

Abstract: This study revealed that commonly used wound dressings dramatically reduce antibacterial activity of clinically used antiseptics and wound irrigating agents in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 17 publications
3
20
0
1
Order By: Relevance
“…Recent research has shown that many wound dressings dramatically reduce the antimicrobial activity of local wound antiseptics and wound irrigating agents ( in vitro data). 19 If the antiseptic properties of wound cleaning agents are also compromised during their clinical use because of possible negative interaction or interference with other wound care products, then an additional component of treatment, including bacterial immobilization, could potentially be beneficial to successfully fight infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that many wound dressings dramatically reduce the antimicrobial activity of local wound antiseptics and wound irrigating agents ( in vitro data). 19 If the antiseptic properties of wound cleaning agents are also compromised during their clinical use because of possible negative interaction or interference with other wound care products, then an additional component of treatment, including bacterial immobilization, could potentially be beneficial to successfully fight infection.…”
Section: Discussionmentioning
confidence: 99%
“…A value of >1 describes good tolerability, while a value <1, poor microbial killing combined with high cytotoxicity. 15 Hirsch et al studied commonly used topical antiseptics, to determine their relative efficacy in terms of minimal inhibitory concentrations and their tissue tolerability. Prontosan (B. Braun, Melsungen, Germany) (discussed later), a polyhexamethylene biguanide (PHMB) product available commercially, for instance, demonstrated excellent efficacy at all concentrations of the "generic" tested (1%-20%), while others required higher concentrations to completely inhibit growth.…”
Section: Topical Antisepticsmentioning
confidence: 99%
“…Povidone iodine products required concentrations in the region of 7.5%-10% to similarly combat P. aeruginosa, and somewhat lower concentrations against Enterococcus faecalis and S. aureus. 15,16 Langer et al have demonstrated that cell microcirculation is also impaired by many of these antiseptic dressings and solutions, resulting in disordered blood vessel leakage, capillary functional densities, and red cell velocity, which may again have profound impact on wound healing. 17 Literature is not widely discussed nor evaluated in the wound practice environment, as much appears contradictory and confusing, particularly with respect to some of the newer wound care products (eg, silver and cadexemer iodine-based products).…”
Section: Topical Antisepticsmentioning
confidence: 99%
“…Polyhexamethylenbiguanind-Derivate (PHMB) waren nur in 32 % der Kombinationen ausreichend antimikrobiell aktiv. In dieser Studie zeigte sich eindeutig, dass häufi g eingesetzte Wundaufl agen die antimikrobielle Wirksamkeit von Antiseptika und Wundspülungen in vitro teilweise drastisch reduzieren können [ 19 ] . Andere Studien haben gezeigt, dass moderne Wundaufl agen keine signifi kante Verbesserung der Wundheilung bewirken.…”
Section: Wechselwirkungen Mit Wundaufl Agenunclassified